Персональні дані та індустріальні дані як об’єкти права власності: оцінка перспектив - Некіт, Катерина Георгіївна; Некіт, К. Г.; Nekit, Kateryna (ВД "Гельветика", 2020)
Статтю присвячено дослідженню можливості поширення на персональні та індустріальні дані правового режиму власності. Проаналізовано GDPR та Директиву (ЄС) 2019/770 з точки зору правового регулювання персональних даних. Виявлено підстави для кваліфікації персональних даних як об’єкту права власності. У статті досліджено поняття індустріальних даних, їх відмінності від персональних даних. Проаналізовано підходи до правового регулювання індустріальних даних. Визначено аргументи на користь поширення на індустріальні дані правового режиму власності. У статті також досліджується проблема визначення, кому саме мають належати права на індустріальні дані.

The article is devoted to the study of the possibility to extend the legal regime of ownership to personal and industrial data. GDPR and Directive (EU) 2019/770 are analyzed in terms of the legal regulation of personal data. Revolutionary in the content of Directive (EU) 2019/770 is the proposal to consider that in some cases personal data is exchanged for digital content and digital services. In fact, this approach gives reason to consider personal data as a kind of currency. Reasons have been identified for qualifying personal data as an object of ownership. Thus, personal data obviously has economic value. At the same time, Ukrainian legislation does not deny the possibility to extend the legal regime of property to intangible goods, such as property rights and obligations. Therefore, one cannot exclude the possibility of recognition of personal data as an object of ownership. The article explores the concept of industrial data, their differences from personal data. The approaches to the legal regulation of industrial data are analyzed. The arguments in favor of extending the legal regime of property to industrial data are determined. In particular, it is noted that industrial data is of economic value and there is a demand for it, therefore, it is increasingly being said that industrial data should become the object of ownership. Such an approach will contribute to the development of a data-based economy. In addition, the provisions on the protection of personal data, intellectual property rights, know-how, databases and so on are not applicable to the legal regulation of industrial data. This requires new solutions. The article also explores the problem of determining to whom the rights to industrial data should belong. The problem is the determination of the person who should own the industrial data – whether it should be a manufacturer, software developer or end user. At the moment, this issue is settled only at the level of contracts, which stipulates that the right to data received by smart things belongs to the end user. The conclusion is made that today, neither personal nor industrial data are defined as objects of property rights at the regulatory level. It is difficult to draw unambiguous conclusions about the possibility of extending the legal regime of ownership of these objects. However, the prospects for solving the problem of determining the legal regime of data are being discussed more and more precisely by recognizing them as objects of ownership.
Некіт, К. Г. Персональні дані та індустріальні дані як об’єкти права власності: оцінка перспектив / К. Г. Некіт // Часопис цивілістики : наук.-практ. журн. / редкол.: Є. О. Харитонов (голов. ред.), О. І. Харитонова (заст. голов. ред.), К. Г. Некіт (відп. секр.), чл. редкол.: С. В. Ківалов, В. В. Завальнюк [та ін.]. – Одеса : Гельветика, 2020. – Вип. 36. – С. 57-64
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; персональні дані; індустріальні дані; промислові дані; Інтернет речей; власність; право власності; інформація; personal data; industrial data; Internet of things; property; ownership; information